2017
DOI: 10.1097/md.0000000000007162
|View full text |Cite
|
Sign up to set email alerts
|

The impact of systemic lupus erythematosus on women's sexual functioning

Abstract: Background:A number of studies have reported the relationship between women's sexual problems and systemic lupus erythematosus (SLE). However, the results are contradictory. The objective of this paper was to explore the impact of SLE on women's sexual function.Methods:PubMed, Web of Science, CNKI Scholar, VIP and WanFang databases were searched up to April 2017. Studies evaluating the impact of SLE on women's sexual function with the use of Female Sexual Function Index (FSFI) scoring system were included. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Both baseline and progression of capillary loss were found to be associated with incident SSc-PAH [1,2]. Both studies reported an association between baseline abnormal capillary morphology and incident SSc-PAH [1,2]. No association with incident SSc-PAH was found between capillary dimension nor presence of haemorrhages [1].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Both baseline and progression of capillary loss were found to be associated with incident SSc-PAH [1,2]. Both studies reported an association between baseline abnormal capillary morphology and incident SSc-PAH [1,2]. No association with incident SSc-PAH was found between capillary dimension nor presence of haemorrhages [1].…”
mentioning
confidence: 98%
“…Its prevalence in Europe is 3.3% in men and 9.9% in women, affecting 15.5% of patients with hand osteoarthritis 1,2 . EO causes a significant loss of function in the hands, with more severe inflammatory signs and affecting almost exclusively the PIP and DIP joints, usually avoiding the TM and MCP.…”
mentioning
confidence: 99%
See 3 more Smart Citations